2019
DOI: 10.1017/s0263574718001406
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid Obstacle-Avoidance Method of Spatial Hyper-Redundant Manipulators for Servicing in Confined Space

Abstract: SummaryDue to a large number of redundant degrees of freedom (DOFs), the hyper-redundant manipulator shows outstanding dexterity and adaptability in avoiding the obstacles in confined space. In this paper, a hybrid obstacle-avoidance method of spatial hyper-redundant manipulators is proposed, with both efficiency and accuracy considered. The space around an obstacle is classified into safe, warning, and dangerous zones. A two-level protection strategy is then addressed to handle the obstacle-avoidance problem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Fahimi et al 14 present a mode shape technique-based approach to resolve the OA problem for hyper-redundant manipulators. Mu et al 15 propose a new strategy named hybrid OA method, which can be used in OA motion planning for hyper-redundant manipulators.…”
Section: Previous Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Fahimi et al 14 present a mode shape technique-based approach to resolve the OA problem for hyper-redundant manipulators. Mu et al 15 propose a new strategy named hybrid OA method, which can be used in OA motion planning for hyper-redundant manipulators.…”
Section: Previous Workmentioning
confidence: 99%
“…It can be observed that the algorithms in the literature 17,39 do not consider the obstacles in the workspaces. In the literature, 7,15,18,33,37 although the proposed approaches can avoid collisions, they cannot be applied to the dynamic working environments. Moreover, the algorithms in Rolf et al 17 and Safeea et al 37 only apply to 2D workspaces.…”
Section: Performance Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Another interesting backbone-curve-based method is presented in ref. [42], with a novel modified modal approach [49]. In this work, the macro shape of the manipulator is constrained by the modified backbone curve.…”
Section: Introductionmentioning
confidence: 99%
“…The application of artificial intelligence methods based on neural networks provides a new idea for manipulator control. These methods are considered to be very promising since its excellent learning ability [22]- [24]. Xu et al [8], [25] propose a novel kinematic controller based on a recurrent neural network (RNN) which is competent in model adaption.…”
Section: Introductionmentioning
confidence: 99%